Exploration of In-vitro antimicrobial and cytotoxic potentials of crude methanolic extracts of Quisqualis indica (stem bark): An ethno medicinal plant - Hossain, Meer; Hussain, Md. Saddam; -UL-Islam, Moin; Abdur Rahman, Md.; Shalahuddin Millat, Md.; Nusrat Sweety, Mirza (International Journal of Biological Research, 2016)
Quisqualis indica plant (Stem bark) was analyzed in-vitro to evaluate biological activities including anti-microbial properties and cytotoxic potentials. The crude n-hexane, carbon tetrachloride, chloroform and aqueous soluble partitionates of the methanolic extract of the plant were subjected to the microbiological investigation against a wide range of Gram positive, Gram negative bacteria and fungi. Brine shrimp lethality bioassay was used for evaluation of cytotoxic activity of Quisqualis indica. The zones of inhibition produced by the hexane, carbon tetrachloride, chloroform and aqueous soluble partitionates of the methanolic extract of Quisqualis indica were ranged from 7-15 mm, 8-18 mm, 12-20 mm and 10-16 mm respectively at a concentration of 400μg/disc. The obtained results were compared against standard Kanamycin (30µg/disc). In case of brine shrimp lethality bioassay, the n-hexane, carbon tetrachloride, chloroform and aqueous soluble partitionates were found to show LC50 of 1.254, 0.826, 3.866 and 5.366 µg/ml respectively as compared with vincristine sulfate (with LC50 value of 0.3229 µg/ml) as a standard positive control. The obtained results confirmed the presence of anti-microbial properties and cytotoxic potentials of Quisqualis indica which supports the traditional use of this plant in various diseases caused by pathogenic microorganisms and can be a good candidate for a further anti-tumor drug study.